The entire sequence over Musielak p-metric space - C. Murugesan; N. Subramanian (Journal of the Egyptian Mathematical Society, 2016)
In this paper, we introduce fibonacci numbers of Γ2(F) sequence space over p-metric spaces defined by Musielak function and examine some topological properties of the resulting these spaces.